COMPARISON OF TWO DOSAGE REGIME OF KETOCONAZOLE IN THE TREATMENT OF PITYRIASIS VERSICOLOR (PV) - Khan, Miraj Muhammad; Noor, Sahibzada Mehmood (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the efficacy and safety of single dose (400 mg) of Ketoconazole versus 10 days 200 mg daily dose of Ketoconazole in the treatment of Pityriasis Versicolor in patients attending out patient department of Hayatabad Medical Complex, Peshawar. Material and Methods: Patients suffering from extensive PV who had not received any other treatment in the last 2 months and having no history of liver disease were selected for this trial. 90 patients (age ranging from 12 to 40 years in both groups) were enrolled for the study during April 2006 till end September 2006. Liver function tests were done before starting treatment, and at intervals of 3 weeks and 6 weeks after therapy. Diagnosis of PV was made on clinical appearance and confirmed by Wood's light examination and KOH examination of mycological scrapings. Patients were divided into 2 groups, A and B. Group A received 200mg of Ketoconazole for 10 days whereas, patients in group B received single 400mg dose. Results: Fifty male patients and 30 female patients completed the study in both groups. 20 patients (50 %) in group A (200 mg daily Ketoconazole for 10 days) had negative mycological and Wood's lamp examination after 3 weeks and 35 patients (87.5%) had negative mycological and Wood's lamp examination after 6 weeks of stopping therapy. While 10 patients (25%) in-group B (400 mg Ketoconazole as single dose) had negative Wood's lamp and mycological cure after 3 weeks while 25 patients (62.5%) had Wood's lamp and mycological cure after 6 weeks of stopping therapy treatment was well tolerated in both groups and none reported any untoward side effects during or after stopping treatment.. Conclsuion: Ketoconazole 200 mg daily for 10 days was found to be more effective in the treatment of PVas compare to single dose therapy of 400mg. However studies involving much larger patients sample are needed to establish the superiority of one form of treatment over the other.